Toughness increase of self compacting concrete reinforced with polypropylene short fibers - G. Melián; G. Barluenga; F. Hernández-Olivares (Materiales de Construccion, 2010)
Increases in bending tests by the addition of low volume fractions of Polypropylene (PP) Short Fibers PP. These toughness increases are similar to those attained by Fiber Reinforced Concrete (FRC) referred elsewhere as Engineered Cementitious Composites (ECC), having some ductility and strain hardening in direct tensile and flexural tests. Concretes mixtures were manufactured using natural pozzolanic blended Portland cement, volcanic crushed coarse aggregates and fine sand from Sahara desert dunes (0-1 mm) from Canary Islands quarries and sand reservoirs, respectively, besides ordinary siliceous sand (0-4 mm) and fly ash from an anthracite-coal heat generator.